2018
DOI: 10.1016/j.pmatsci.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Towards the design of high-performance plant fibre composites

Abstract: For the past 15 years, there has been tremendous and ever-increasing industrial and academic interest and technological material development concerning plant fibre reinforced composites.Plant fibres can be sourced from a multitude of natural agro-sources, with the preferred choice as a composite reinforcement material often being driven by abundance, geographical location, and historical use. While from a product designer's or engineer's point of view, all plant cell walls are 'similar', there is indeed substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
246
3
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 338 publications
(289 citation statements)
references
References 411 publications
(597 reference statements)
23
246
3
4
Order By: Relevance
“…In terms of stiffness, the addition of scutched flax enhanced both tensile and flexural moduli of PA6 significantly. The modulus increase is expected because the reported elastic modulus of flax is 45–60 GPa . However, the extent of stiffness enhancement is dictated by the processing methodology.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In terms of stiffness, the addition of scutched flax enhanced both tensile and flexural moduli of PA6 significantly. The modulus increase is expected because the reported elastic modulus of flax is 45–60 GPa . However, the extent of stiffness enhancement is dictated by the processing methodology.…”
Section: Resultsmentioning
confidence: 99%
“…revealed that the lack of compounding kept the flax fibers in MIXsc mostly in their original, bundled technical fibers state. Based on previous studies that have reported slightly lower tensile modulus for technical fibers (~45 GPa) in reference to elementary fibers (60 GPa) , the E f quantity in Eq . is then an averaged technical/elementary fiber stiffness, which would be lower for MIXsc than SSSPsc.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations